Price of life i.e. costs of treatment of neoplastic diseases of blood - Wiktor Jędrzejczak, Wiesław (Contemporary Oncology/Współczesna Onkologia, 2000)
Essential goals of therapy of neoplastic blood disorders, principles of cost analysis including three major disease related groups such as: acute leukemias and myelodysplastic syndromes, lymphomas, and chronic myeloproliferative disorders were reviewed. Subsequently, the results of cost analysis were shown divided into main phases of therapy and main components. They were analyzed in context of reimbursement quotas imposed by the Mazovian Regional Health Insurance Authority. Furthermore, these results were discussed in the context of published costs of similar procedures in the U.S., as well as in the context of prices of non-medical products in Poland and in the U.S. In general, identical medical procedures (utilizing the same drugs and manouvers) cost many times less in Poland while the non-medical prices (food and industrial products) are similar.